Cardiac, skeletal muscle and serum irisin responses to with or without water exercise in young and old male rats: Cardiac muscle produces more irisin than skeletal muscle - Aydin, Suna; Kuloglu, Tuncay; Aydin, Suleyman; Eren, Mehmet Nesimi; Celik, Ahmet; Yilmaz, Musa; Dabak, Ozlem (Elsevier Science Inc, 2014)
Irisin converts white adipose tissue (WAT) into brown adipose tissue (BAT), as regulated by energy expenditure. The relationship between irisin concentrations after exercise in rats compared humans after exercise remains controversial. We therefore: (1) measured irisin expression in cardiac and skeletal muscle, liver, kidney, peripheral nerve sheath and skin tissues, as also serum irisin level in 10 week-old rats without exercise, and (2) measured tissue supernatant irisin levels in cardiac and skeletal muscle, and in response to exercise in young and old rats to establishing which tissues produced most irisin. Young (12 months) and old rats (24 months) with or without 10min exercise (water floating) and healthy 10 week-old Sprague-Dawley rats without exercise were used. Irisin was absent from sections of skeletal muscle of unexercised rats, the only part being stained being the perimysium. In contrast, cardiac muscle tissue, peripheral myelin sheath, liver, kidneys, and skin dermis and hypodermis were strongly immunoreactivity. No irisin was seen in skeletal muscle of unexercised young and old rats, but a slight amount was detected after exercise. Strong immunoreactivity occurred in cardiac muscle of young and old rats with or without exercise, notably in pericardial connective tissue. Serum irisin increased after exercise, being higher in younger than older rats. Irisin in tissue supernatants (cardiac and skeletal muscle) was high with or without exercise. High supernatant irisin could come from connective tissues around skeletal muscle, especially nerve sheaths located within it. Skeletal muscle is probably not a main irisin source. Copyright (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Irisin; Cardiac and skeletal muscle; Skin; Nerve sheath; Liver; Kidney